Suntingan Teks dan Pengembangan Ilmu Humaniora: Text Editions and Development of Humanities Studies - Nurhata Nurhata; Sri Wulandari (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
The number of Nusantara manuscripts is exceptionally abundant, and these are preserved in various countries, held by both institutions and private individuals. Some of these manuscripts have undergone philological study and have been published digitally and physically by governmental or educational institutions. Nevertheless, the results of philological study in the form of text edition have been widely utilized, particularly by disciplines within the humanities. This research employs a qualitative method, an explorative design, with a descriptive analytical approach. As a working hypothesis, the utilization of text editions should consider several factors. First, since philological studies often focus on codicological and textological aspects, it is necessary to first ascertain their relevance to the research needs, many of which are already registered in manuscript research catalogues. Second, for studies in literature, culture, and liguistics, a fundamental understanding of ancient scripts and languages, as well as the content and writing context, is required to properly confirm previous studies. Third, text editions can serve as historilah argumentation and a foundation for the development of literary, linguistic, and cultural research, the patterns of which can be observed in a number of previous studies.